Development of creative entrepreneurship: Opinion of managers from Estonia, Latvia, Finland and Sweden - Küttim, Merle; Arvola, Katrin; Venesaar, Urve (Business: Theory and Practice, 2011)
Due to the nature of the creative sector, which consists of a large number of SMEs and self-employed or part-time employees operating in complex and dynamic environment, the creative enterprises face a number of difficulties and are in need of support. The current study was carried out in the framework of an INTERREG project “Creative Entrepreneurship Training Network – CREAENT”. The sample of the study consisted of 74 creative managers from Estonia, Latvia, Finland and Sweden. For data collection structured interviews were carried out. The method of data analysis was thematic content analysis. The creative entrepreneurs found that their weaknesses lay in different entrepreneurial competences. The best ways of acquiring entrepreneurial competences were education and experience, also communication and networking. The aspects that satisfied the creative entrepreneurs about entrepreneurship courses were useful knowledge, suitable teaching methods, new contacts and networks, and creative industry specialised courses. The unsatisfying factors were out-dated and too theoretical knowledge, unsuitable teaching and learning methods and not enough creative industry courses. The future entrepreneurship courses should provide soft skills like communication, negotiation and conflict management; attention should be paid to creative industry specific problems and needs, ways of implementing knowledge in practice, enabling dialogue and peer-teaching among participants.